The role of preceding technical and tactical skills on jump shot accuracy in male and female basketball players - Argiriou, M.; Rousanoglou, E.; Boudolos, K.; Bolatoglou, T. (Journal of Athletic Enhancement, 2014)
Preceding skill is often identified as a critical factor in jump shot (JS) accuracy, but research confirmation remains limited. Men`s superiority invites an assumption of gender differences regarding skills preceding a JS. The present study aimed to investigate the effect of preceding technical and tactical skill on JS accuracy among male and female basketball players. Notational analysis was applied to videotaped games (six top-ranking men`s and women`s teams, Greek National Basketball Championship, 2009-2010). Five technical skills (shooting distance, ball pick up, number of dribbles, hand of last dribble, motion of pass receiver, footwork) and four tactical skills (on ball screen, off ball screen, court sides of pass origin and destination, court areas of pass origin and destination) were examined. Preceding defensive pressure was also recorded. Gender difference was tested on attempted and accurate JS percentages (Custom Tables, SPSS 21.0, p = 0.05). Cross-tabulation and the Pearson Chi-square were used to test the significance of the relation between preceding skill and JS accuracy (SPSS 21.0, p = 0.05). Significant gender differences of attempted and accurate JS percentages were found in respect of technical and tactical skills (p = 0.05). In men, JS accuracy was related to tactical (p = 0.05) but not to technical ( p>0.05) skills. Conversely, in women, JS accuracy was predominantly related to technical skills, with a single observed tactical correlation for court areas of pass origin and destination (p = 0.05). These results indicate a differing by gender role of preceding technical and tactical skill on JS accuracy. Tactical skills can be seen as the "training window" that would give women a winning advantage by integrating technical skills into their team work as effectively as men.